Pemberdayaan Kelompok Wanita Tani Melalui Pelatihan Pembuatan Pupuk Organik Cair untuk Fase Vegetatif Tanaman - Lolyta Sisillia; Dwi Astiani; Wiwik Ekyastuti; Emi Roslinda; Hanna Artuti Ekamawanti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aimed to enhance the capacity of the Women Farmers Group (KWT) in understanding, producing, and applying locally sourced Liquid Organic Fertilizer (LOF) to support plant growth during the vegetative phase. The program employed a participatory approach consisting of socialization, training, and evaluation stages. Evaluation was conducted using questionnaires and observation sheets, and the data were analyzed descriptively using qualitative and quantitative percentage-based methods. The initial survey revealed that only 43% of participants had previously used LOF, 6% had produced it, while 97% expressed willingness to learn how to produce LOF. The training results demonstrated an improvement in participants’ knowledge and skills in LOF production, as well as the emergence of community initiatives to implement LOF in crop cultivation. The findings indicate that the community service program successfully enhanced the capacity of the KWT to utilize local organic materials as natural fertilizer sources and strengthened awareness of the importance of sustainable agricultural practices based on local resources.